Does caffeine matter for arousal? Affective and autonomic responses induced by caffeine in coffee intake: evidence from a double-blind tasting task - Rodrigues, Fernando (2022)
Coffee is consumed worldwide, but there are different types of espresso blends, each with its unique concentration of caffeine, which can have different effects on the human being. The aim of this study was to understand the effect of the impact of caffeine on the autonomic nervous system, evaluating the physiological changes and subjective responses due to different levels of caffeine intake. A double-blind tasting task consisting of one within-subject factor design (caffeine level: high / double caffeine mixture (blend A) vs single-charge caffeine mixture (blend B) vs low-caffeine mixture (blend c) allowed us to assess participants’ autonomic responses using Heart Rate Variability (HRV) and Pupillary Reactivity (PR). Arousal was also assessed through the Self-Assessment Manikin (SAM). Results revealed statistically significant differences in HRV and PR between coffee blends, showing the blend A,a more pronounced autonomic response that blend C. However, no significant differences were found in arousal level among coffee blends. These results are similar to previous research that pointed out to a discordance between subjective and objective measures when caffeine is consumed.